PENERAPAN PENDEKATAN CTL UNTUK MENINGKATKAN KAPASITAS BERPIKIR KRITIS MATEMATIK PESERTADIDIK DI TINGKAT SMP - eko Agustianto (IKIP Siliwangi, 2018)
The research objective is to examine the achievement of mathematical critical thinking capacity of students applying the CTL approach with a comparison of students applying ordinary learning and examining the extent to which the increasing capacity of critical thinking in mathematics students apply the CTL approach to the comparison of students who apply ordinary learning. The study population was all junior high schools in West Bandung regency, were chosen arbitrarily and were selected by Darul Hikmah Junior High School. The sample is taken by any selected class of class 7-A as a research class, and class 7-B as a review class. The research class is given a learning model with the CTL approach, and the review class is given an ordinary learning model. The research instruments used in mathematical critical thinking capacity tests take the form of descriptions. Data processing increases the capacity of critical thinking mathematically by applying tests that distinguish two means using IBM SPSS 23 software. Data from the analysis showed that the achievement and improvement of the critical thinking capacity of the mathematics of the participants who were given the learning method using the CTL approach was better than those of the participants who were given the usual learning method.